NATURE’S CORNER - Larsen, Ellinor; Kando, Yuko; Algasra, Mussa (My University, 2023)
Collaboration Sufficient spaces for collaboration work on different scales. These spaces should be placed near the examination rooms for quick access and increased usage. Sound privacy The workspaces should have sound privacy in order for the staff to concentrate. Sound privacy is also needed when discussing a patient or having a phone call. Equality Today the majority of staff in healthcare environments are women but in the future it might be a more equal division.The spaces for staff should be designed gender neutral in order to futureproof the building. Nature The project should supply the surrounding neighborhood with nature that promotes people to be outside. Nature has shown to have a great impact on mental and physical wellbeing. Exercise The environment accessible for the public should promote physical activity. This could be outside of the building to reach the entire neighborhood and not only the listed patients. Education The environment should provide learning about health and how to improve your own wellbeing. Easy orientation The space should be easy to navigate. The patients should not have to walk through long corridors with a lot of turns alone in order to find their way around. Participation Involving the patients as much as possible in their treatment and health status. “Person centered care means close involvement around and with the patient. This means the need to work with information and documentation within the patient room. Privacy The person should always have the option to sit more secluded and should not feel watched or unsafe in the examination room. Anxiety and stress relief The environment should strive to have a calming effect on the nervous system.